Ketergantungan Mahasiswa Universitas Jember Terhadap Artificial Intelligence (AI) - Sirah Robitha Maula; Sindi Dewi Aprillian; Assyfa Wahida Rachman; Meutia Nur Marziah Azman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Currently, humanity is entering an era where various technological advances greatly influence their daily lives, especially in the field of education. Media progress can be felt through media that can help humans carry out all their activities, for example looking for entertainment online, studying online, communicating online, and so on. For those who sell, media can be used to assist in the product promotion process which involves online media or social media. Among several forms of development in today's technology is the increasingly powerful artificial intelligence (AI) which is developing significantly and has an impact on the world of education. GPT Chat is an AI that is widely used by students. This research is based on concerns about students who are dependent on using Chat GPT, namely that they may experience a decline in their thinking ability because they are used to using help to do each task. The aim of this research is to increase knowledge about whether some students who often use GPT Chat in their lectures can be said to be dependent on this. The theoretical perspective used in this research is the theory of Structural Functionalism by Talcott Parsons. There are four functional imperatives for all systems, which actions are called the "AGIL" scheme, namely: Adaptation (A) Adaptation, Goal Attainment (G) Achievement of goals, Integration (I) Integration, and Latency (L) Latency or pattern maintenance. In this research, the method used is a qualitative research method with an ethnographic approach and a data collection process in the form of observation, interviews and documentation. The informants studied were 5 people who were students at the University of Jember. The results of the research are that Jember University students know in general about Artificial Intelligence (AI), namely a computer system whose capabilities are equivalent to the human brain and functions to help human work. In this case, students use Artificial Intelligence (AI), especially Chat GPT to help with their assignments. In terms of use, students have never experienced any difficulties. Regarding dependence on the use of Artificial Intelligence (AI), students do not use this technology continuously, but only when they lack inspiration in carrying out assignments. The answers they get are also not always accurate, which sometimes makes students need to add answers other than those from Chat GPT. Then, if you use Artificial Intelligence (AI) technology too often, especially Chat GPT, it can make students even more lazy to think critically.